LEADERSHIP STYLE ANALYSIS AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE REGIONAL RESEARCH AND DEVELOPMENT PLANNING AGENCY OF MESUJI REGENCY - R Bambang (Saburai International Journal of Social Sciences and Development, 2022)
The research carried out is descriptive quantitative research. This study used 35 research respondents. There are three variables in this study, namely: 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable where Leadership Style (X1) and Work Discipline (X2) as independent variables and Employee Performance (Y) as dependent variable . The method used is primary data and secondary data. Based on the results of data analysis, it has been found that the answers to the hypothesis are as follows; There is an influence of Leadership Style (X1) on Employee Performance (Y) with an influence level of 42.9%. There is an influence of Work Discipline (X2) on Employee Performance (Y), with an influence level of 36.4% There is an influence of Leadership Style (X1) and Work Discipline (X2) on Employee Performance (Y), with an influence level of 52.8%